Selective Synthesis of cis and trans o-Hydroxychalcone Derivatives for Metal Sensing Applications - Md Rakibul Islam; Md Kabidur Rahman; Md Mizanur Rahman Badal; Md Maniruzzaman; Mohammad Abu Yousuf (Journal of Chemistry, 2025)
This study explores a novel synthetic approach for obtaining cis- and trans-isomers of o-hydroxychalcone derivatives and their metal-sensing capabilities. Four chalcones (CH-1 to CH-4) were synthesized using an optimized Claisen–Schmidt condensation reaction. This method efficiently yielded the desired products by combining o-hydroxyacetophenone with various substituted benzaldehydes in the presence of NaOH. The key innovation lies in the reaction conditions that enable the selective synthesis of both cis- and trans-isomers. Analysis of the allylic protons in CH-1, CH-2, and CH-3 using 1H NMR revealed a coupling constant (JHα-JHβ) of 15.60 Hz, confirming their trans configuration. Conversely, CH-4 displayed a coupling constant of J = 8.40 Hz, indicating a cis configuration. Further structure optimization was performed using the B3LYP method with a DFT B3LYP/Lan2DZ level of theory. The metal-sensing properties and selectivity of the synthesized chalcones were evaluated using UV-Vis spectroscopy in an ethanolic solution containing various metal ions (Cu2+, Fe3+, Zn2+, K+, Mn2+, and Co2+). Interestingly, CH-1 and CH-2 exhibited specific interactions with Cu2+ ions. In contrast, CH-3 and CH-4 demonstrated the ability to sense both Cu2+ and Fe3+, highlighting their potential for dual metal ion detection. This work presents a novel synthesis method for controlling cis-trans isomerism in o-hydroxychalcones and unveils their promising uses in selective metal ion–sensing applications.